The fate of concomitant mild mitral regurgitation in aortic insufficiency: A neglected subject - Xu, Hao; Guo, Ruiming; Liu, Donghai; Hou, Suyun; Qiao, Chenhui; Zhang, Xin (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Mitral regurgitation (MR) is commonly experienced by patients with aortic insufficiency (AI) and in its mild form is considered benign. However, the progression of concomitant mild regurgitation after the aortic valve surgery (AVS) for AI is poorly characterized. The current study aimed to define long-term outcomes of MR after surgery and identify risk factors involved in deterioration. Methods: Patients presenting with moderate/severe AI and concomitant mild MR (n=347) between January 2013 and December 2021 were enrolled. MR grade was assessed by transthoracic echocardiography during the follow-up and deterioration defined as an increase in grade to moderate or severe MR by the last follow-up echocardiography. Analysis of risk factors for early mortality, MR deterioration and long-term mortality were performed. Results: 278 patients (84.8%) among 328 survivals had at least one follow-up echocardiography, and complete follow-up occurred for 316 patients (96.3%). Mild MR improved to trivial or none in 194 patients (69.8%), progressed to persistent mild MR for 74 patients (26.6%) and deteriorated for 10 patients (3.6%). Preoperative atrial fibrillation (odds ratio (OR), 23.09; 95% confidence interval (CI), 4.35-122.54) and rheumatic AI (OR, 11.61; 95% CI, 1.26-106.85) were shown to be independent risk factors for MR deterioration by generalized linear mixed analysis. Conclusion: Progression of concomitant mild MR is rare in patients with AI after AVS. However, rheumatic AI and preoperative atrial fibrillation increase the probability of MR deterioration. Careful follow-up for this cohort of patients is recommended.